Perovskite: Scintillators, direct detectors, and X-ray imagers. (May 2022) - Jana, Atanu; Cho, Sangeun; Patil, Supriya A.; Meena, Abhishek; Jo, Yongcheol; Sree, Vijaya Gopalan; Park, Youngsin; Kim, Hyungsang; Im, Hyunsik; Taylor, Robert A.
Graphical abstract: Abstract: Halide perovskites (HPs) are used in various applications, including solar cells, light-emitting diodes, lasers, and photodetectors. These materials have recently received a great deal of attention as high-energy radiation detectors and scintillators due to their excellent light yield, mobility-lifetime product (µτ), and X-ray sensitivity. In addition, due to their solution-processability and low cost, perovskite materials could be used to produce thick perovskite films across wide areas, allowing for low-dose X-ray imaging. Perovskite-based scintillators and detectors could eventually replace commercialized products like thallium‐doped cesium iodide (CsI:Tl) and amorphous silicon (Si). Here, we review all of the key properties of HPs, the relevant terminology necessary for radiation detection and scintillation, the physical mechanisms underlying their operation, the fabrication process, and perovskite crystals and thin-films of varying dimensionality used for high-energy radiation detection. We also cover the critical issues and solutions that HPs as detectors, scintillators, and imagers face.